The combined measurement of 87Sr/86Sr isotope ratios and 88Sr/85Rb elemental ratios using laser ablation MC-ICP-MS and its application for food provenance studies: the case for Asturian beans. Issue 5 (24th April 2018) - Reguera-Galan, Aida; Moldovan, Mariella; Garcia Alonso, J. Ignacio
Abstract : By combining the 87 Sr/ 86 Sr isotope ratio with the 88 Sr/ 85 Rb elemental ratio the discrimination between Asturian and South American beans was possible. Abstract : The spectral interference of 87 Rb on 87 Sr for the measurement of 87 Sr/ 86 Sr isotope ratios in solid samples by laser ablation multicollector (MC)-ICP-MS could be corrected by combining the transient signal of the sample with a Rb pulse from the nebulisation of a pure Rb standard. This dual sample introduction system, combined with a multiple linear regression data treatment procedure, allowed the interference free measurement of the 87 Sr/ 86 Sr isotope ratio in solid samples. Additionally, when the signals for Rb and Sr could be separated in time, even only partially, the application of the multiple linear regression procedure allowed us to compute also the 87 Sr/ 86 Sr isotope ratio free of spectral interference. The fact that Sr was concentrated in the seed coat of beans, whereas Rb was mainly present in the cotyledon, allowed us to develop a laser ablation multicollector ICP-MS procedure for the authentication of Asturian beans which are subject to fraud with the import of South American beans. By combining the 87 Sr/ 86 Sr isotope ratio with the 88 Sr/ 85 Rb elemental ratio we were able to distinguish between Asturian and South American beans in spite of the large 87 Sr/ 86 Sr isotopic variability of Asturian beans.